Dinonemertes shinkaii sp. nov., (Nemertea: Hoplonemertea: Polystilifera: Pelagica) a new species of bathypelagic nemertean - Kajihara, Hiroshi; Lindsay, Dhugal J. (Zootaxa, 2010)
A new species of bathypelagic polystiliferous nemertean Dinonemertes shinkaii is described based on the holotype obtained by the manned submersible Shinkai 6500 from a depth of 2343 m in Japan Trench, Northwest Pacific. Dinonemertes shinkaii can be distinguished from its congeners in having a translucent body, 24 proboscis nerves, two pairs of intestinal caecal diverticula, and about 25 pairs of intestinal lateral diverticula. This species represents the first dinonemertid to have pseudostriated muscle fibres in the rhynchocoel circular muscle layers.